Peran Guru Kelas Dalam Mengembangkan Karakter Religius Siswa Di Madrasah Ibtidaiyah Khairul Anwar Desa Sana Laok Kecamatan Waru Kabupaten Pamekasan Madura - Asyari, Moh. (IJIT: Indonesian Journal of Islamic Teaching, 2022)
Education has a massive role as a center of excellence in preparing human character to face the Times's challenges. Character education in elementary school should intensify attention to strengthen the principle of akhlakul karimah. This is done so that students are aware of the urgency of virtue values and commit and hold fast always to do the next virtue in their daily lives. Therefore, teachers have a significant role in character education; religious characters must start from elementary school or madrasah Ibtidaiyah because if the holy symbol is not formed starting from childhood, it will be difficult to change one's personality.